Somatic Mutations in UBA1 Define a Distinct Subset of Relapsing Polychondritis Patients With VEXAS. Issue 10 (31st August 2021) - Ferrada, Marcela A.; Sikora, Keith A.; Luo, Yiming; Wells, Kristina V.; Patel, Bhavisha; Groarke, Emma M.; Ospina Cardona, Daniela; Rominger, Emily; Hoffmann, Patrycja; Le, Mimi T.; Deng, Zuoming; Quinn, Kaitlin A.; et al.
Abstract : Objective: Somatic mutations in UBA1 cause a newly defined syndrome known as VEXAS (vacuoles, E1 enzyme, X‐linked, autoinflammatory, somatic syndrome). More than 50% of patients currently identified as having VEXAS met diagnostic criteria for relapsing polychondritis (RP), but clinical features that characterize VEXAS within a cohort of patients with RP have not been defined. We undertook this study to define the prevalence of somatic mutations in UBA1 in patients with RP and to create an algorithm to identify patients with genetically confirmed VEXAS among those with RP. Methods: Exome and targeted sequencing of UBA1 was performed in a prospective observational cohort of patients with RP. Clinical and immunologic characteristics of patients with RP were compared based on the presence or absence of UBA1 mutations. The random forest method was used to derive a clinical algorithm to identify patients with UBA1 mutations. Results: Seven of 92 patients with RP (7.6%) had UBA1 mutations (referred to here as VEXAS‐RP). Patients with VEXAS‐RP were all male, were on average ≥45 years of age at disease onset, and commonly had fever, ear chondritis, skin involvement, deep vein thrombosis, and pulmonary infiltrates. No patient with VEXAS‐RP had chondritis of the airways or costochondritis. Mortality was greater in VEXAS‐RP than in RP (23% versus 4%; P = 0.029). Elevated acute‐phase reactants and hematologic abnormalities (e.g., macrocytic anemia, thrombocytopenia, lymphopenia, multiple myeloma, myelodysplastic syndrome) were prevalent in VEXAS‐RP. A decision tree algorithm based on male sex, a mean corpuscular volume >100 fl, and a platelet count <200 ×10 3 /μl differentiated VEXAS‐RP from RP with 100% sensitivity and 96% specificity. Conclusion: Mutations in UBA1 were causal for disease in a subset of patients with RP. This subset of patients was defined by disease onset in the fifth decade of life or later, male sex, ear/nose chondritis, and hematologic abnormalities. Early identification is important in VEXAS given the associated high mortality rate.